Job Expectancy of LIS Students after Graduation - ZAHED BIGDELI; seyede sedigheh taherzadeh mousavian; shabnam shahini (توسعه اجتماعی)
This research attempted to investigate job expectancy of LIS students. The survey is of a descriptive-analytical type. The population consisted of LIS students in government universities. 700 questionnaires were distributed and 640 were returned; however, 610 were used in analyzing the data. Four faculty members confirmed the validity of the questionnaire and its reliability was measured through Cronbach’s Alpha, 0.89. He results showed that, in general, job expectancy of students is at a “moderate” level. Students’ hope to find jobs relevant or semi-relevant to their field of study is significantly lower than “average”; however, their hope to get “any” job is higher than “average”. Respondents believe that university enrolment, departmental facilities, and the Ministry’s policies influence job opportunities. It was also found that the chance to get a “relevant’ job in one year time span after graduation, is less than getting a job” irrelevant” to their field of study or “any” job. Students did not have a positive view to find a job in a short time, especially a job relevant to their field of study. This belief might be a reason for students not to be motivated to be serious in their studies. It is essential for those responsible to think and plan to change the present job opportunities in the country; otherwise, the country unfortunately will suffer more and more.